Wtórny rynek książki w Polsce : instytucje, asortyment, uczestnicy - Nieć, Grzegorz (Księgarnia Akademicka Publishing, 2016)
THE SECONDARY BOOK MARKET IN POLAND The concept of the secondary book market comprises institutions and processes related to the antiquarian bookseller’s assortment that has been published and introduced into trading at least once beforehand or, in other words, all library materials that have already been sold or published by a widely defined originator. The originator is here widely understood, because the said assortment includes traded items that are not only books, though they constitute the majority, but also all library materials, i.e.. manuscripts, official documents etc., as well as items of a completely different nature, e.g. stationery and artworks. This research covers all known institutions and forms of assortment exchange, its composition and the structure of the offer, sources and methods of sourcing, preparation and marketing as well as sale and the market participants. The latter can generally be divided into service providers (vendors, brokers, organisers of the exchange, experts) and service recipients (the selling party and the buying party), although many participants often play both roles. A special emphasis has been placed on customers who are very active buyers, i.e. bibliophiles, collectors and libraries. Non-commercial activity of stationary antiquarian bookshops seen as cultural institutions is also taken into account.